Synthesis and insecticidal activities of novel bridged-neonicotinoids - Zhang, Dong-Dong; Cui, Shu-Xia; Xu, Zhi-Ping; Li, Dong-Mei; Tian, Zhong-Zhen (Chinese chemical letters, 2017)
A series of novel bridged-neonicotinoid analogues were designed and synthesized, which were constructed by starting material 8 with cyclopentenone or cyclohexenone in the presence of catalyst aluminium chloride. All of the compounds were characterized and confirmed by~1H NMR,~（13）C NMR, HRMS and IR. The bioassay tests showed that compounds 5 and 6a showed higher bioactivities than imidacloprid against Aphis craccivora.